PENGARUH PERSEPSI WAJIB PAJAK MUSLIM TERHADAP POTONGAN PAJAK ATAS ZAKAT PENGHASILAN DI INDONESIA (Studi Empiris Wajib Pajak Muslim di Kabupaten Kendal) - Barda Rajaza Musaif; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2020)
The purpose of this research are to identify Muslim taxpayers’ perception towards tax rabate over income zakat payments in Indonesia and explain the factors that affect it. This research uses data collection  methods  with a  closed  questionnaire  and  a  total  number  of  100  respondents  into  the research sample. The answer of closed questions that represent the observed variables were then being analyzed by value of Structural Equation Modeling which is run by AMOS 22 programme. From the results of the questionnaire, this research found that important to know the halal status of the tax rabate on zakat paid, the legal consciousness of a person, and the religiosity of a person plays a role in giving positive perceptions toward tax rabate over zakat payments.  However, if seen from the results of the model formed by SEM analysis, it’s found that halal-haram aspects and religiosity of taxpayers  are  positive  significant  factor  for  growing  perceptions  toward  tax  rabate  over  zakat payments, but legal consciousness are not significant factor for growing perceptions toward   tax rabate over zakat payments. This research was conducted in the context of proposed tax policy. This research will definitely play an important role for the countries or tax policy makers related to zakat, and academics in understanding the perception of Muslim taxpayers towards tax rabate over income zakat payments in Indonesia.